Selenite reduced cadmium uptake, interfered signal transduction of endogenous phytohormones, and stimulated secretion of tartaric acid based on a combined analysis of non-invasive micro-test technique, transcriptome and metabolome - Wu, KongYuan (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.